The Journal of Intervention and Statebuilding Ten Years on: Critical Reflections and Stimulating Ideas on an Evolving Scholarship. Issue 1 (2nd January 2016) - Aaronson, Michael; Ahram, Ariel I.; Duffield, Mark; Etzioni, Amitai; Holland, Jack; Mac Ginty, Roger; McLeod, Laura; Podder, Sukanya; Richmond, Oliver P.; Roberts, David
ABSTRACT: The Journal of Intervention and Statebuilding celebrates its tenth anniversary this year. This special volume opens up with a selection of nine of the most influential articles published in the journal. JISB's editorial team has asked the authors for their reflections on their original articles, telling us more about the writing process at that time, what they would do differently (with hindsight), or how they see their articles contributing to current debates on intervention and statebuilding. We have selected one article per volume, and we have ordered the contribution starting from volume 1 (2007) to volume 9 (2015). The articles will be made open access for the year, and we highly recommend (re-)reading the original articles along with the comments from the authors.